Immune Efficacy and Intestinal Microbiota of Rainbow Trout ( Oncorhynchus mykiss ) After Inactivated IHNV Vaccination via Distinct Injection Regimens - Zhiyuan Luo; Jie Li; Caixia Shan; Yu Ning; Yanyan Luo; Mingzhou Zhang; Wenwen Zhang; Lining Ren; Zhe Liu; Jianfu Wang (Journal of Fish Diseases, 2026)
This study optimised the immunisation protocol for rainbow trout fingerlings against infectious haematopoietic necrosis virus (IHNV). Fish were administered an experimental vaccine via intraperitoneal injection, consisting of formalin‐inactivated IHNV formulated with Montanide ISA 763A VG. A 2 × 2 factorial design was employed to compare two injection volumes (50 μL or 150 μL) and two immunisation regimens (single versus double injection). Serum neutralising antibody titres, splenic expression of six immune‐related genes ( TLR7 , MyD88 , IRF7 , IFN‐α , IgM , Mx‐1 ), and gut microbiota composition were assessed before and after IHNV challenge. A double immunisation regimen with 50 μL elicited the highest antibody titres and the most robust post‐challenge upregulation of all target genes, whereas administration of 150 μL alone yielded inferior outcomes. 16S rRNA gene sequencing revealed Proteobacteria and Cyanobacteria as the predominant bacterial phyla across all treatment groups. Immunisation significantly reduced the abundance of potentially pathogenic taxa (e.g., Flavobacterium , Vibrio ) and increased that of Pseudomonas and Acinetobacter , indicating enhanced intestinal homeostasis and antiviral gene expression. Collectively, a two‐dose regimen with 50 μL maximises systemic immunity, strengthens mucosal defence and supports a balanced gut microbiota, providing a practical and effective strategy for IHNV control in rainbow trout aquaculture.